2002
DOI: 10.1038/ng837
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 regulates the G2/M checkpoint by activating Chk1 kinase upon DNA damage

Abstract: The breast cancer tumor-suppressor gene, BRCA1, encodes a protein with a BRCT domain-a motif that is found in many proteins that are implicated in DNA damage response and in genome stability. Phosphorylation of BRCA1 by the DNA damage-response proteins ATM, ATR and hCds1/Chk2 changes in response to DNA damage and at replication-block checkpoints. Although cells that lack BRCA1 have an abnormal response to DNA damage, the exact role of BRCA1 in this process has remained unclear. Here we show that BRCA1 is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
357
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(388 citation statements)
references
References 23 publications
18
357
0
6
Order By: Relevance
“…In contrast, the ATM-dependent IR inducible S-phase checkpoint required S1387 of BRCA1 but not S1423. And, as noted above, BRCA1 regulation of the G2/M DNA damage checkpoint occurred through its ability to activate the Chk1 kinase and, thereby, induce molecular events downstream of Chk1 (Yarden et al, 2002).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, the ATM-dependent IR inducible S-phase checkpoint required S1387 of BRCA1 but not S1423. And, as noted above, BRCA1 regulation of the G2/M DNA damage checkpoint occurred through its ability to activate the Chk1 kinase and, thereby, induce molecular events downstream of Chk1 (Yarden et al, 2002).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 83%
“…The ability of BRCA1 to rescue cell survival following IR appears to be dependent, in part, on the S988 phosphorylation. Finally, it was demonstrated that funcional BRCA1 is required for the activation of Chk1 kinase, a major component of the DNA damage-responsive G2/M cell cycle checkpoint (Yarden et al, 2002) (see below). Li et al (2000) have described another potential functional interaction between ATM and BRCA1 in response to IR and other genotoxic stresses.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%
“…Interestingly, Claspin levels are lower in BRCA1-deficient cells, indicating that the BRCA1-pathway may be involved in regulation of Claspin. As BRCA1-deficient cells have a defect in Chk1 activation (Yarden et al, 2002), the lower Claspin levels are possibly due to a defect in Chk1 activation. This agrees with our observation that blocking Chk1 activity in wild-type BRCA1 reconstituted cells inhibits the BRCA1-dependent increase of Claspin expression in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…HCC1937 cells have a defect in Chk1 activation (Yarden et al, 2002), since BRCA1 is required for efficient Chk1 activation following DNA damage. One possible explanation is that the reduced levels of Claspin in HCC1937 cells are due to the lower levels of activated Chk1 in these cells.…”
Section: Chk1 Regulates Claspin Levelsmentioning
confidence: 99%
“…P21 can specifically inhibit nuclear activity of Cdc2-Cyclin B, whereas 14-3-3 sequesters Cdc2-Cyclin B preventing it from entering the nucleus. The G2/M checkpoint also upregulates Wee1, which leads to an increase in inhibitory phosphorylation on Cdk1-Cyclin B (Yarden et al, 2002). Furthermore, ATM and ATR dependent Plk1 inactivation has been shown, which most likely prevents activation of Cdc25C by phosphorylation (Smits et al, 2000;van Vugt et al, 2001).…”
Section: G2/m Phase Transition Checkpointmentioning
confidence: 99%